Mobilizing climate finance for effective operationalization of climate-smart agriculture institutional innovations in West and Central Africa - Ganyo, Komla Kyky; Kpadonou, G Esaie; Segnon, Alcade Christel; Ngaido, Amadou; Sobgui, Caroline Makamto; Lamien, Nieyidouba; Zougmore, Robert Bellarmin (2025)
Accelerating the scaling of climate-smart agriculture (CSA) requires institutional innovations and interactions among stakeholders, operating across scales, for aligning actions and advocacy for enabling policy environment. Since 2022, AICCRA has been supporting the revitalization and operationalization of the West Africa CSA Alliance (WACSA) and the Central Africa CSA Alliance (CACSA), two institutional innovations operating at regional scale and aimed at facilitating dialogue and discussions among stakeholders on CSA, as well as fostering collective actions to transform and reorient agricultural systems through CSA. This infonote documents the outcomes and lessons learnt from a series of stakeholder engagement workshops which brought together 74 experts in agriculture sector from 19 countries in West and Central Africa regions and 31 institutions, including national and international research institutes, ministry of agriculture and regional farmer organizations to review the actions selected, plan and budget for two regional CSA programs formulated to operationalize the two CSA alliances. While both regions are exposed to climate risks, CSA programming, investment and actions require a nuanced understanding of the region’s agroecological diversity, socioeconomic conditions, and climate vulnerabilities. West Africa’s CSA program prioritized agriculture and food system adaptation with mitigation co-benefits, whereas Central Africa focused on mitigation through forest restoration and agroforestry with adaptation co-benefits. About 25 and 21 million USD are needed to implement two regional CSA programs in West and Centra Africa regions respectively. Tailored financial instruments, bundled technologies and know-how, development of digital tools, capacity building, and inclusive governance mechanisms are essential to ensure that CSA investments not only address climate risks but also leverage the unique ecological and economic opportunities of West and Central Africa.